Bending Strength of Steel Bracket and Splice Plates - Mohr, Benjamin A.; Murray, Thomas M. (Engineering Journal, 2008)
The primary purpose of this study was to determine the ultimate behavior of bracket and splice plates. The study consisted of experimental testing and comparison of test results with various design methods. The experimental testing consisted of connecting two beams together with web splice plates to form a simple span, then loading the span symmetrically to induce pure moment at the location of the splice with the goal of achieving plate flexural rupture. This study indicates that design models used prior to the publication of the 13th Edition AISC Steel Construction Manual for determining bracket plate and web splice nominal moment strength are overly conservative.